On some classes of non-commutative dimonoids - Gavrylkiv, V. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 512.53We study  dimonoids, i.e., algebraic structures with  two associative binary operations satisfying a given system of axioms. We analyze the properties of dual dimonoids. In the class of non-commutative dimonoids, we construct numerous Abelian, non-Abelian, and rectangular dimonoids. The structure of these objects is analyzed, their automorphism groups and halos are computed.